Analisis Hubungan Faktor Personal Pelaku dengan Tindak Pidana Penyalahgunaan Obat di Wilayah Provinsi Bali - Juniarka, I Gede Agus; Umbasniajati, Enny Undari (Jurnal Farmasi Udayana, 2025)
Criminal acts in drug abuse tend to increase every year. Some of the most frequently abused drugs in recent years are psychotropic drugs and certain prescription drugs. (OOT). In generally, the factors that cause these crimes can be divided into two factor, first personal factors ( originate from within the individual) and situational factors. Studies related to the analysis of the causes of drug abuse crime have not been much done, especially in the province of Bali. The study aims to analyze the relationship between the personal factors of the perpetrators and drug abuse crimes in the province of Bali. The data used is data of pro-justicia cases related to drug abuses crimes handled by BBPOM in Denpasar and the Local Office in Buleleng (as an investigator and expert) during the period January 2021 to February 2024. Spearman's descriptive analysis and correlation tests were carried out against these factors. The result was that the frequency of drug crimes was dominated by the abuse of OOT commodities (89.5%) with the predominant personal factors, namely the age group 20-24 years (31.6%), the type of occupation (57.9%), and the level of high school education (36.8%). Spearman's correlation test results showed that there was a correlationship between the commodity of this crime drug with the age of the perpetrator (0.551) and the kind of job (0.604), whereas on the factor level of education there was no relationship (0.033) (P = 95%). A correlation value > Alpha (0,05) indicates that between compared factors there is a correlationship. The absence of correlation to the educational level factor, indicates that any level of education, has equal chances of being exposed to drug abuse crime. Similarly, in connection with the correlation between the age factor and the type of job, it becomes a reference and consideration for BPOM, the Bali Regional Police, and the Bali Provincial Government in determining a more effective, effective, and targeted preventive action strategy to reduce the rate of drug abuse.